1993
DOI: 10.1159/000147430
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Damping Effect of Different Shoeing by the Measurement of Hoof Acceleration

Abstract: The purpose of this study was to compare the damping effect of 16 types of shoeing by measuring hoof acceleration parameters on two trotting horses. At impact, maximal deceleration had extreme values such as 188 m/s2(± 55) for the most damping combination (p < 0.01) and 746 m/s2 (± 14) for the steel shoe (mean = 551 m/s2 ± 125). After the shock, the hoof was exposed to a mean vibrating acceleration at 418 Hz (± 84) which was progressively damped in 37.3 ms (± 10.5). According t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1
2

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 4 publications
4
49
1
2
Order By: Relevance
“…35 Compared to the reference steel shoe, shock reduction was higher for light shoes made of a polymer and/or aluminum alloy which had lower stiffness values and density than steel (Fig. 2.5.13).…”
Section: Effects Of Shoeingmentioning
confidence: 88%
See 1 more Smart Citation
“…35 Compared to the reference steel shoe, shock reduction was higher for light shoes made of a polymer and/or aluminum alloy which had lower stiffness values and density than steel (Fig. 2.5.13).…”
Section: Effects Of Shoeingmentioning
confidence: 88%
“…[34][35][36] An accelerometer could be fi xed on the hoof wall in order to measure the maximal deceleration of the hoof impact on the ground and the vibration frequency ( Fig. 2.5.6).…”
Section: Acceleration Analysismentioning
confidence: 99%
“…The natural frequency of 1744 Hz was more than five times greater than the 260 Hz cutoff frequency, a bandwidth considered sufficient for the study of the hoof strike at a gallop (Benoit et al, 1993). Because the usable bandwidth of an undamped second order system is about 20% of the natural frequency without the need to correct for instrument dynamics (Doebelin, 1990), the natural frequency was sufficiently high.…”
Section: Article In Pressmentioning
confidence: 99%
“…Design criteria for a dynamometric horseshoe must take specific environmental factors into account. Hoof height varies from 0.9 to 1.0 cm between shoeings (Dyce et al, 1987;Josseck et al, 1995), and a racing plate can be up to 1.8 cm thick with a toe grab (Benoit et al, 1993;Kane et al, 1996) and heel traction devices, leaving a shoe thickness of up to 2.8 cm possible without altering shoeing parameters beyond those found during training. Aluminum racing plates weigh about 0.1 kg (Kane et al, 1996), with their steel training counterparts weighing 0.3 kg.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations have shown that acceleration measurement is a suitable method to find differences in the stress on the horse's limb caused by various shoeing [1,2] or different surfaces [3][4][5][6][7][8]. Measurement data, such as acceleration-time curves, often include noise that influences the results.…”
Section: Introductionmentioning
confidence: 99%